The Evolution of Hutchinsonian Climatic Niche Hypervolumes in Gymnosperms - Fernanda S. Caron; Jānis Lazovskis; David F. R. P. Burslem; Juliano Morimoto (Global Ecology and Biogeography, 2026)
Aim The niche is a fundamental concept in theoretical and experimental ecology and is used to describe a wide range of ecological processes from species' interactions with the environment to community assemblies. A common way to represent the niche is through a multidimensional geometry known as the Hutchinsonian niche hypervolume. Ecological theory predicts that niche hypervolumes have properties such as holes with broader eco‐evolutionary significance, but we lack a comprehensive empirical study of niche hypervolume properties and their evolutionary meaning. Location Global. Time Period Holocene. Major Taxa Studied Gymnosperms. Methods We conducted for the first time a systematic and comprehensive test of the evolution of Hutchinsonian climatic niche hypervolume properties (volume and holes) across 418 species, 65 genera, and 12 families of gymnosperms, which includes many species that are endangered or threatened. Using cutting‐edge computational algorithms, we measured the evolution of geometric (i. e., volume) and topological (i. e., holes) properties of gymnosperm hypervolumes across a comprehensive calibrated phylogeny. Results Our comparative analysis revealed moderate evidence of the non‐independent evolution of niche hypervolume and no evidence of the non‐independent evolution of holey hypervolumes across gymnosperm species. We also found that species, genera and families with low hypervolume volume, such as monotypic groups like Gingko , likely experienced shifts in hypervolume evolutionary rates. However, our analysis of niche positioning showed that climatic distances between co‐occurring species did not significantly depart from null expectations, suggesting that their spatial distribution within the climatic space is independent of limiting similarity. Main Conclusions Our results indicate that topological properties of gymnosperm climatic niche hypervolumes show little phylogenetic constraint and thus arise as emergent outcomes of species–environment interactions. In contrast, the breadth of environmental occupancy (hypervolume volume) retains a moderate evolutionary signal. These patterns suggest that while the capacity to occupy wider or narrower climatic conditions is moderately shared by evolutionary history, the actual realisation of these niches is not driven by significant climatic divergence.